The Effect of Learning Motivation on English Learning Outcomes at the State of High School 2 Sungai Lilin - Bambang Purwanto, Muhammad (STIT Buntet Pesantren Cirebon, 2022)
Based on the results of initial observations, student learning outcomes in English subjects are still not optimal. This can be seen from the acquisition of an average student score of 67, which is still below the predetermined KKM of 70. This problem tends to be influenced by the lack of learning motivation that students have during the learning process, which has an impact on learning English outcomes. This research uses mixed methods. There are 2 types of data analysis tests, simple correlation tests, and descriptive analysis. Based on the results of research and discussion, the conclusions of this study are as follows. 1) The learning motivation of the tenth graders of SMAN 2 Sungai Lilin is good. This is evident from the acquisition of an assessment score of 80.21% in English learning motivation, which is in the good category. Thus, students' motivation in learning English has increased and is categorized as